Conditionality of the application of certain labor law norms to regulate the work of foreign workers - Belozerova, К.А. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2021)
The article under consideration, using the example of the labor legislation of the Russian Federation, describes the procedure for applying certain provisions of regulatory legal acts to regulate the work of employees who are foreign citizens and stateless persons, in cases where the application of such norms involves administrative procedures, including those in force in the state of the employer for foreign citizens and stateless persons. As part of the consideration of this issue, the impact of administrative procedures, primarily provided for in the Russian Federation by migration legislation and legislation on the legal status of foreign citizens and stateless persons, on the application of labor law norms, the impact of the status of a foreign citizen and a stateless person on the mechanism of action of labor law norms, the achievement of the goals of their application is determined. Based on the analysis, it is concluded that their actions are conditional in relation to employees who are foreign citizens and stateless persons, and in some cases, the creation of prerequisites for discrimination by such a mechanism of action both in relation to a special category of employees and in relation to employees who are Russian citizens. In some cases, the regulatory regulation provided for by the legislation of the Republic of Kazakhstan is considered as a more successful option of adaptation within the framework of the implementation of administrative procedures of the legal status of a foreign citizen to the status of an employee.